2008
DOI: 10.1155/2008/690535
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Biological Activities of Cu(II), Co(II), Ni(II), Mn(II) and Fe(III) Complexes with Schiff Base Derived from 3‐(4‐Chlorophenoxymethyl)‐4‐amino‐5‐mercapto‐1,2,4‐triazole

Abstract: Coordination complexes of Cu(II),Co(II), Ni(II), Mn(II) and Fe(III)with Schiff bases derived from 3-(4-chlorophenoxymethyl)-4-amino-5-mercapto-1, 2, 4-triazole and substituted aldehydes have been synthesized. The complexes were characterized by elemental analysis, conductivity measurements, magnetic susceptibility data, electronic, IR, ESR and1H NMR spectral data. On the basis spectroscopic studies, the Schiff base is monobasic bidentate ligand having the composition ML2(2H2O) Where M = Cu(II), Co(II), Ni(II) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Triazoles are widely known to possess broad-spectrum biological activities such as antibacterial [1][2][3][4] , antifungal [5][6][7][8] , anticonvulsant [9][10][11] , antitumor [12][13][14] , antitubercular [15][16][17][18][19] , antimicrobial [20][21][22][23][24] , anticancer [25][26][27] , analgesic 28 , cytotoxic 29 , insecticidal, herbicidal, plant growth regulatory [30][31][32] , and antiproliferative activities 33,34 . These are extensively used as prospective ligands in a variety of bioinorganic syntheses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Triazoles are widely known to possess broad-spectrum biological activities such as antibacterial [1][2][3][4] , antifungal [5][6][7][8] , anticonvulsant [9][10][11] , antitumor [12][13][14] , antitubercular [15][16][17][18][19] , antimicrobial [20][21][22][23][24] , anticancer [25][26][27] , analgesic 28 , cytotoxic 29 , insecticidal, herbicidal, plant growth regulatory [30][31][32] , and antiproliferative activities 33,34 . These are extensively used as prospective ligands in a variety of bioinorganic syntheses.…”
Section: Introductionmentioning
confidence: 99%
“…Brine shrimp bioassay data of the ligands (L 1 -L 5 ) and their metal(II) complexes(1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…They coordinate to the metal ion in many ways, depending upon the nature of the functional groups [8][9][10][11] . Studies have indicated that many triazole derived Schiff bases show antibacterial [12][13][14] , antifungal 15,16 , antimicrobial [17][18][19][20] , anticancer 21,22 , analgesic 23 , anticonvulsant 24 , antitumor [25][26][27] , antitubercular [28][29][30][31] , insecticidal, herbicidal, and plant growth regulatory [32][33][34] activities. Due to increased interest in the chemistry of vanadyl compounds and the potentially bioactive nature of triazoles, we have made an effort to combine the chemistry of vanadium(IV) with newly synthesized triazole Schiff bases L 1 -L 5 (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Two absorption bands appeared at 2850-2800 cm -1 are due to mCH asymmetric and symmetric stretching and the frequency bands, which appear at 1620-1600 cm -1 are due to N-H bending mode. The mC-H out of plane bending vibration of aromatic system is seen in 770-750 cm -1 range [26,27]. The band observed at 1195-1170 and 1280-1215 cm -1 are assigned to C-N of barbituric acid and phenolic C-O stretching vibration, respectively, which get shifted to lower frequency in all the polymer metal complexes and consistent with coordination via the protonated phenolic oxygen [28].…”
Section: Infrared Spectramentioning
confidence: 80%